(untitled) (Al-Aasar, 2025)
This research explores the psychological dimensions of Dawah (Islamic outreach) and the principle of Ri’ayat al-Fitrah (observing human nature) within the framework of Quranic communication. The core objective is to analyze how the Quranic discourse aligns with the innate human disposition (Fitrah) to facilitate effective communication and behavioral change. By employing a qualitative and analytical approach, the study examines the psychological structures of the human soul as defined by the Quran—namely the Nafs (levels of the soul), Qalb (heart), and Fu’ad (insight)—and their roles in receiving or resisting divine messages. The research highlights key Quranic communicative strategies such as Qawl-e-Sadid (straightforward speech), Qawl-e-Layyin (gentle speech), and Hikmah (wisdom), correlating them with modern psychological concepts like Cognitive Dissonance, Emotional Intelligence, and Behavioral Gradualism. Furthermore, the study investigates the impact of Quranic parables (Amthal) and storytelling (Qasas) as tools for mental imagery and subconscious moral cultivation. In the contemporary context, the paper addresses digital challenges, emphasizing the principle of Tabayyun (verification) to counter misinformation and comparing the empathetic depth of human-led Dawah with Artificial Intelligence. The findings suggest that Quranic communication is not merely an informational exchange but a sophisticated psychological intervention designed to achieve Mutma’innah (psychological equilibrium). The research concludes that for modern practitioners of Dawah, success lies in understanding the recipient’s psychological predispositions and socio-cultural context, ensuring that the divine message resonates with the inherent truth residing within the human soul.